Application of the Steepest Ascent Hill Climbing (SAHC) Algorithm for Mobile-based Shortest Route Search - Mhd Furqan; A Armansyah; Razzaq H. Nur Wijaya (IJISTECH (International Journal of Information System and Technology), 2020)
This study aims at early to determine the application of algorithms Steepest Ascent Hill Climbing (SAHC) for finding the shortest route-based Mobile in Humbang Hasundutan. Based on the results of the application of algorithms Steepest Ascent Hill Climbing (Sahc) To search based Shortest These Mobile in Humbang Hasundutan. So it can be concluded that the search for the shortest route based on Mobile can be solved using the Steepest Ascent Hill Climbing algorithm. In the manual calculation process using the Steepest Ascent Hill Climbing algorithm at the node from Humbang, there is a heuristic value of 0.0896184808, at the node from which the three intersections are originated there is a heuristic value of 0.1693780561, at the node from which there is a heuristic value of 0.367474152, at the node from which the waterfall falls sibabo has a heuristic value of 0.3823982675. Then the result of the shortest route from Sipinsur Geosite (F) to Simolap Waterfall (B) is F èD èB (Sipinsur GeoSite - intersection 4 - Simolap Waterfall) the total distance is 51 km and the time is 1 hour 34 minutes. So that the test results of the Steepest Ascent Hill Climbing algorithm process with the system in accordance with the manual calculation process of the Steepest Ascent Hill Climbing algorithm.